Penggunaan Metode Triple Exponential Smoothing Tipe Brown dalam Meramalkan Pergerakan Kasus Positif Covid-19 di Kota Padang - Nurul Umiati Husna; Arnellis Arnellis (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Covid-19 is an infectious disease that caused by SARS-CoV-2 virus. This virus can cause the patient gotten respiratory problems, such as Pneumonis, SARS, and MERS. The amout of Covid-19 cases have been increased everyday. Therefore, it is necessary to do forecasting for the movement of positive Covid-19 cases in Padang City for the next few days. The purpose of this research was to find out the form of a model for the movement of positive Covid-19 cases in Padang City and to know the results of the movement of positive Covid-19 cases in Padang City. The type of this research is applied research. The method that used in this research is Triple Exponential Smooting Brown Type with the parameter of α that minimize the value of MSE was 0,29. The results of this research showing the movement of positive Covid-19 in Padang City from August 15, 2020 to August 19, 2020 was 907, 933, 960, 987, and 1016 cases. Keywords — Covid-19, The movement of positive cases, Forecasting, Triple Exponential Smoothing Brown Type.